Wild and Domestic Differences in Plant Development and Responses to Water Deficit in Cicer - Berger, Jens; Pushpavalli, Raju; Ludwig, Christiane; Parsons, Sylvia; Basdemir, Fatma; Whisson, Kelly (Frontiers in Genetics, 2020)
There is growing interest in widening the genetic diversity of domestic crops using wild relatives to break linkage drag and/or introduce new adaptive traits, particularly in narrow crops such as chickpea. To this end it is important to understand wild and domestic adaptive differences to develop greater insight into how wild traits can be exploited for crop improvement. Here we study wild and domestic Cicer development and water-use over the lifecycle, measuring responses to reproductive water deficit, a key Mediterranean selection pressure, using mini-lysimeters (33l round pots) in common gardens under contrasting water regimes. Wild and domestic Cicer were consistently separated by later phenology, greater water extraction and lower WUE and harvest index in the former, and much greater yield-responsiveness in the latter. Throughout the lifecycle there was greater vegetative investment in wild, and greater reproductive investment in domestic Cicer, reflected in root and harvest indices, rates of leaf area and pod growth. Domestic WUE was consistently greater than wild, suggesting differences in water-use regulation and partitioning. Large wild-domestic differences revealed in this study are indicative of evolution under contrasting selection pressures. Cicer domestication has selected for early phenology, greater early vigour and reproductive efficiency, attributes well-suited to a time delimited production system where the crop is protected from grazing, disease and competition, circumstances that do not pertain in the wild. Wild Cicer attributes are more competitive: higher peak rates of leaf area growth, greater ad libitum water-use and extraction under terminal drought associated with greater vegetative dry matter allocation, leading to a lower reproductive capacity and efficiency than in domestic chickpea. These traits strengthen competitive capacity throughout the growing season and are likely to facilitate recovery from grazing, two significant selection pressures faced by wild, rather than domesticated Cicer. While increased water extraction may be useful for improving chickpea drought tolerance, this trait must be evaluated independently of the other associated wild traits. To this end wild-domestic populations have been developed.